Showdown in the Big Quiet : Land, Myth, and Government in the American West - Bieter, John P., Jr (Book collections on Project MUSE., 2015)
""Examines the area known as the Big Quiet, the role of environment, the history of this area in the West, and the power of Western mythology"--Provided by publisher.